Macrophage-extracellular matrix interactions: Perspectives for tissue engineered heart valve remodeling - Poulis, Nikolaos; Martin, Marcy; Hoerstrup, Simon P.; Emmert, Maximilian Y.; Fioretta, Emanuela S. (Frontiers in Cardiovascular Medicine, 2022)
In situ heart valve tissue engineering approaches have been proposed as promising strategies to overcome the limitations of current heart valve replacements. Tissue engineered heart valves (TEHVs) generated from in vitro grown tissue engineered matrices (TEMs) aim at mimicking the microenvironmental cues from the extracellular matrix (ECM) to favor integration and remodeling of the implant. A key role of the ECM is to provide mechanical support to and attract host cells into the construct. Additionally, each ECM component plays a critical role in regulating cell adhesion, growth, migration, and differentiation potential. Importantly, the immune response to the implanted TEHV is also modulated biophysically via macrophage-ECM protein interactions. Therefore, the aim of this review is to summarize what is currently known about the interactions and signaling networks occurring between ECM proteins and macrophages, and how these interactions may impact the long-term in situ remodeling outcomes of TEMs. First, we provide an overview of in situ tissue engineering approaches and their clinical relevance, followed by a discussion on the fundamentals of the remodeling cascades. We then focus on the role of circulation-derived and resident tissue macrophages, with particular emphasis on the ramifications that ECM proteins and peptides may have in regulating the host immune response. Finally, the relevance of these findings for heart valve tissue engineering applications is discussed.